Efforts To Strengthen Community Businesses Through Mosques During The Covid-19 Pandemic In Banda Aceh City - Kamaruddin, Kamaruddin; Fakhruddin, Fakhruddin (Al-Fikrah, 2024)
This research is related to the problem of the mosque-based ummat economy, Banda Aceh is one of the areas that has economic potential through the mosque both in this case is the capital of various businesses, then the land and potential of human resources but its utilization is very minimal. This research uses qualitative research methods with an analytical descriptive approach, this research was conducted through data collection techniques with observation and interviews. The results of the research Efforts The potential of the mosque from the gallery and souvenir business is the target of tourist guests from outside both local and foreign by coming to buy souvenirs. After the covid-19 virus appeared, the souvenir business unit was closed and is no longer running until now because there are no visitors and buyers. BKM is thinking of building a new business unit that can support the mosque's operations, of course, there is an empty waqf land owned by the mosque which is located behind the mosque, we opened a culinary shop kuala ulee lheu as a culinary tour that can support the mosque's operations. The mechanism of the BKM management proposes this program to BKPRMI Aceh, the involvement in this business is the BKM mosque management and also some people who help in managing the culinary shop business unit. The Bank Indonesia institution helped in the cost of building a business unit which they had previously coordinated with the BKM management.